Prinsip-Prinsip mengenai “Hidup Bebas Dari Jerat Hutang” Berdasarkan Studi Tematik Amsal 10-20 - Adji Kurniawan; Tulus Raharjo (Sekolah Tinggi Teologi Injili Indonesia Yogyakarta, 2022)
Modern-day Christians live in the face of the fact that the world's financial system is heavily influenced by debt. To understand the principle of living free from debt bondage, it is not only a matter of how a person can pay off his debts, but how he has a good character and lives in the guidance of God's wisdom. That is why the author conducted a study of the Book of Proverbs, because the Book of Proverbs is not only full of poetic beauty and soft nuances full of meaning in life, it also contains the wisdom of God from ancient times which is still relevant today which fills all its pages. This study uses the wisdom hermeneutic method to find 3 (three) principles to prevent someone from falling into debt, namely: First, the principle of a guarded heart; Second, the principle of an expert hand; and Third, the principle of a trusted mouth.